The travel, equity and wellbeing impacts of transit-oriented development in Global South. (December 2022) - Wang, Fenglong; Zheng, Yuya; Wu, Wenjie; Wang, Donggen
Abstract: Transit-oriented development (TOD) has been widely introduced in the Global South countries and drawn growing scholarly attention. This paper critically reviews and concisely summarizes the research findings pertaining to the travel, equity and wellbeing impacts of TOD in the Global South. We identify 53 relevant studies and find that TOD increases public transportation ridership and promotes subjective well-being. However, similar to what happens in the Global North, TOD in the Global South also induces gentrification and unexpected social inequalities. We call for more critical and theoretical discussions about the uniqueness of TOD in Global South and application of more sophisticated methods and more detailed indicators to better explain the impacts of TOD. Future studies may also be fruitful to investigate some new topics, such as the role of state in TOD-induced gentrification, residential dissonance in TOD areas and hedonic adaptation to the improvement in transit services.